RELASI CINTA DALAM TASAWUF - Suwito Suwito (Fakultas Ushuluddin dan Humaniora, Universitas Islam Negeri Walisongo Semarang, Indonesia, 2013)
Abstract: This article discusses the relationship of love in the Sufi perspective. Opositorum Coindencia theory is used to dissect this relationṢip , so that the devil Sufism is seen as a